Peer-feedback as a Translation Training Tool in Web-based Communication - Flanagan, Marian; Heine, Carmen (HERMES - Journal of Language and Communication in Business, 2015)
Teaching web-based communication involves website analysis, website design and webcopy writing, often in multiple languages for different target audiences. Localization and foreign language webcopy writing require training in the area of translation, in addition to other skills related to web communication. Such training might be didactically supported with peer-feedback assignments. Surprisingly few studies in the area of localization/translation and web-based communication report about classroom practice of this kind. Drawing on theory from Educational Psychology, Writing Research in L2 and Translation Studies, this paper explores common notions in peer-feedback research. It discusses peer-feedback and its implementation as a translation training tool in the context of web-based communication with a focus on localization as a form of text production. Student feedback and the revisions performed on its basis are investigated. The data reported here derive from an undergraduate web-based communication course, where students produced a translation and an academic translation review. The paper discusses possible future peer-feedback practices, including suggestions for feedback scaffolding tailored to the needs of future language professionals in the area of web-based communication.